Persepsi Wisatawan terhadap Kualitas Fasilitas dan Daya Tarik Aktivitas Surfing di Pantai Sorake Nias Selatan - Nija Sinedesis Hia; Fahd Mukhtarsyaf; Alimuddin; Donal Syafrianto; Ridho Bahtra (MAN Insan Cendekia Jambi, 2026)
This study aimed to describe tourists’ perceptions of facility quality and the attractiveness of surfing activities at Sorake Beach, South Nias Regency. A descriptive quantitative design was applied in June 2026. One hundred domestic and international tourists were selected through accidental sampling, with eligibility limited to visitors who had participated in or were participating in surfing activities. Data were collected using a four-point Likert questionnaire covering facility quality and surfing attraction, supported by observation, interviews, and documentation. The data were analyzed using means and percentages. The results showed that facility quality achieved a mean score of 1.99 and was categorized as poor. The main weaknesses concerned facility condition and maintenance, toilet cleanliness, safety equipment, tourist information, and emergency health services. In contrast, the attractiveness of surfing activities achieved a mean score of 2.63 and was categorized as good. Exciting surfing experiences, alignment with visitor expectations, wave quality, and the coastal landscape were the most appreciated aspects. The study concludes that Sorake Beach’s strong surfing attraction has not been fully supported by adequate amenities. Improvements in cleanliness, maintenance, multilingual information, safety facilities, and emergency services require collaboration among government, destination managers, tourism businesses, and local communities.